Trends in Bullying and Emotional and Behavioral Difficulties Among Pakistani Schoolchildren: A Cross-Sectional Survey of Seven Cities - Naveed, Sadiq; Waqas, Ahmed; Shah, Zarnain; Ahmad, Waqas; Wasim, Muhammad; Rasheed, Jawaria; Afzaal, Tayyaba (Frontiers in Psychiatry, 2020)
Background Bullying and peer victimization among adolescents are growing public health concerns that affect victims’ emotional well-being, and their social and academic functioning. Despite concerns about this public health epidemic in low- and middle-income countries, most prevalence, policy and intervention studies have been conducted in developed countries and economies. Methods This cross-sectional study was conducted between September 2016 and July 2017 at seven public and private schools located in five districts in Pakistan: Lodhran, Rahim Yar Khan, Bahawalpur, Faisalabad, Multan, Thatta and Nawabshah. A total of 2315 schoolchildren were surveyed with a specially designed instrument in Urdu with items about demographics and bullying behavior, together with a strengths and difficulties questionnaire. Results Mean age of the respondents was 14.63 (2.87) years. More than half of the respondents were males (n = 1301, 56.2%), and a majority reported that their mothers were housewives (n = 2100, 90.7%). A total of 615 (26.6%) respondents reported being bullied at school, and 415 (17.9%) reported being bullied away from school. Perpetration of bullying was reported by 430 (18.6%) participants at school and 376 (16.3%) away from school. Being bullied in the past was strongly associated with becoming a perpetrator of bullying in the future. Internalizing symptoms were significantly associated with male gender, older age, being a victim of bullying, and employment status of the respondent’s mother. Externalizing symptoms were significantly associated with male gender, older age, being a victim and perpetrator of bullying, and mother’s employment status. Conclusion Bullying perpetrators have a greater tendency to exhibit externalizing symptoms, whereas victims develop both externalizing and internalizing psychopathologies.